PROTECTION OF WITNESS JUSTICE COLLABORATORS IN CRIMINAL ACTIONS - Rachmad Abduh (International Journal Reglement & Society (IJRS), 2021)
Article 1 point 27 of the Criminal Procedure Code explains that witness testimony is one of the means of evidence in a criminal case in the form of testimony from a witness regarding a criminal event that he heard himself, he saw for himself and himself by mentioning the reasons and his knowledge. Based on this, proving is a way of proving before the court. Thus, proving is evidence. Evidence is the most important piece of evidence in the examination of criminal cases. almost all evidence of criminal cases is always based on the examination of witnesses. Information is the first evidence that is mentioned in the Criminal Procedure Code (KUHAP), in general, there is no case that escapes the evidence of witness evidence. Almost all case evidence always relies on witness examination, at least in addition to evidence with other evidence, evidence is always required with witness evidence. Basically all activities in the legal process for the settlement of criminal cases, from the investigation until the final decision is pronounced before the trial by the panel of judges, are activities related to evidence or activities to prove. Although the law of proving criminal cases focuses on the process of proving activities in court, the process of proving already exists and begins at the time of the investigation. Even at the time of the investigation, an initial work in carrying out the criminal case process by the state.